The formation mechanisms of sedimentary pyrite nodules determined by trace element and sulfur isotope microanalysis. (15th August 2019) - Gregory, Daniel; Mukherjee, Indrani; Olson, Stephanie L.; Large, Ross R.; Danyushevsky, Leonid V.; Stepanov, Aleksandr S.; Avila, Janaina N.; Cliff, John; Ireland, Trevor R.; Raiswell, Robert; Olin, Paul H.; Maslennikov, Valeriy V.; et al.
Abstract: Redox sensitive trace elements in pyrite, including nodules, are increasingly used to infer the chemical conditions of ancient oceans—but considerable uncertainty remains regarding the mechanism and timing of nodule formation. Resolving these uncertainties is important because pyrite nodules must form in connection with the overlying water column, rather than during late diagenesis, to reflect the composition of the global ocean. Existing models for pyrite nodule formation have been specific to pyrite textures from individual sites, and we lack a unified model that can explain the compositional and textural diversity observed in nodules from different localities. In this study we examine ten pyrite nodules from several geological periods (Neoarchean to Carboniferous) using in situ LA-ICP-MS and SHRIMP-SI analyses. We present transects of spot analyses of trace elements (As, Ag, Cu, Co, Ni, Sb and Se) and S isotope ratios for each nodule. The pyrite nodules can be classified according to three main categories: those with (1) little to no trace element or isotopic zonation of the nodule from core to margin, (2) strong zonation from core to margin, and (3) minor zonation near the core but more significant zonation near the margin of the nodule. We further illustrate this zonation with a NanoSIMS element map from an additional pyrite nodule. These results are interpreted to indicate nodule formation along a spectrum between two end-member mechanisms. We suggest that the absence of trace element or isotopic zonation reflects nodule growth by a pathway that is analogous to the pervasive growth mechanism for carbonate nodules. This model involves the production of many nucleation sites that are evenly distributed within the volume that the nodule eventually occupies. Consequently, this mechanism results in a chemically homogenous nodule. Pyrites formed this way are suitable for paleoceanographic reconstruction. The other end-member mechanism is analogous to the concentric growth model for carbonate concretions. In this scenario, the core of the nodule forms first and is followed by the addition of concentric layers—each with a progressively different trace element content and δ 34 S signature as diagenesis progresses. Despite having limited utility for reconstructing ancient seawater, these late forming nodules may track the evolving availability of bioessential trace elements for the subsurface biosphere with important implications for global biogeochemical cycles. Spatial trends in trace elements and S isotopes thus speak to the mechanisms of pyrite nodule formation and provide a framework for evaluating nodule suitability for a range of paleoenvironmental studies.